Pengaruh Brand Awareness Dan Service Quality Terhadap Keputusan Pembelian Pada Konsumen Mixue Munjul Majalengka - Z nur, Latief; Prihartini, Endah; Cahya Sudarman, Septian Dwi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The large number of food and beverage businesses in Indonesia indicates that the level of purchasing decisions in Indonesia is high. The high enthusiasm of the community makes companies have to compete to attract the attention of consumers so that consumers make purchases. One of the things a company can do to attract the attention of consumers is Brand Awareness. If consumer awareness of the brand is low, then it is certain that the brand equity will also be low. The other factor that also influences the purchasing decision is Service Quality. Good Service Quality will affect profit and correlate with the results that will be obtained by a company. This study aims to determine the effect of Brand Awareness and Service Quality on purchasing decisions for consumers of Mixue, Munjul Majalengka Branch. The method used in this research is descriptive and verification method. The population used is the consumer Mixue Branch Munjul Majalengka with a sample of 100 people with a sampling technique using non-probability sampling with accidental sampling. Data collection technique is by questionnaire. The analytical tools used in this study are the classical assumption test, multiple linear regression, coefficient of determination (R2), Model Feasibility (f test) and Hypothesis Test (t test). Based on the results of this study, it shows Brand Awareness has a positive and significant effect on purchasing decisions and Service Quality has a positive and significant effect on purchasing decisions.